Aid attitudes in short- and long-term perspectives among Ukrainian migrants and Poles during the Russian war in 2022 - Kyliushyk, Ivanna; Jastrzebowska, Agata (Frontiers in Sociology, 2023)
The aim of this article is to diagnose aid attitudes among those who potentially need help—help receivers, i. e., Ukrainian refugees—and help givers, i.e., Poles and Ukrainian labor migrants, during the initial stage of the escalation of the Russian war in 2022. By aid attitudes, we mean approaches to both the offering and the acceptance of help during the war in the short and long term. We conducted a small-scale exploratory web survey (Computer-Assisted Web Interview—computer-assisted interview using a website) from March to June 2022, in which the main aims were to explore the needs and offers for both, short- and long-term aid and the gaps between them. Respondents were asked about different types of aid without indicating from whom they wanted to receive this help: the state, NGOs or individuals offering their help. The survey results show discrepancies in what migrants need and what is offered to them in Poland, both from the short and long-term perspectives.